Evaluation of emissions of CO2 and air pollutants from electric vehicles in Italian cities. (1st November 2015) - Donateo, T.; Licci, F.; D'Elia, A.; Colangelo, G.; Laforgia, D.; Ciancarelli, F.
Highlights: Environmental impact of electric vehicles with Plant-To-Vehicle approach. Statistical analysis of recharges in Rome in 2013. Emission factors (g/kW h) for Italian power plants at full and partial loads. Electricity generation mix for each recharging event. Comparison with limits set for conventional vehicles by European legislation for CO2 and pollutants. Abstract: The paper analyzes data about recharge of electric cars in Rome during 2013 as a part of a national research project (P.R.I.M.E.). The electric vehicles were recharged through the public Enel Distribuzione recharging infrastructure. For each recharge, the initial and final time were registered together with the electricity absorbed from the grid. The total number of recharges was about 7700. The first step of the investigation is the statistical analysis of the distribution of recharges in daily time slots in order to analyze the recharge behavior of Italian drivers. For each day and for each time slot, literature data from the Italian national grid operator (Terna) were used to retrieve the energy mix used to produce electricity in that day and in that time slot. In the third step, electricity generation mixes were used to obtain emission factors for greenhouse (CO2 ) and pollutant emissions (CO, NO x, HC and particulate). Using information about the electric consumption of vehicles registered in Rome, the emission factors in g/km were obtained and compared with the limits set by European legislation for conventional (gasoline and diesel).